Senam Sebagai Upaya Meningkatkan Kesehatan Fisik Lansia - Ita Novianti; Asrianti Safitri Muchtar; Mutmainnah Mutmainnah; St. Malka (Lembaga Pengembangan Kinerja Dosen, 2023)
Elderly is a man or woman who has entered the age of 60 years accompanied by various declines in physical condition, decreased function of the body's organs, and decreased function of the brain. The elderly population is increasing globally. Service activities aim to empower the elderly through elderly gymnastics as an effort to improve physical health in supporting the Tangguh elderly. The method of activity in this service involves 5 students of midwifery Akbid Batari Toja. The service implementation adopts action research steps which consist of 4 (four) stages, namely: planning, action, observation and evaluation, and reflection. Evaluation of the results of the conclusion, namely the implementation of community service with a series of activities, namely checking blood pressure and exercising for the elderly. Before being given information regarding elderly exercise, all 28 elderly participants did not know about elderly exercise movements. After being given information on elderly gymnastic movements, as many as 25 elderly people followed the gymnastic movements and did them correctly. Based on the results of blood pressure checks, it was found that 7 elderly people had high blood pressure ≥ 140/100, the community service team recommended carrying out examinations at the nearest health center, advising them to consume lots of vegetables and fruit and routinely doing elderly exercises.